A prompt radio transient associated with a gamma-ray superflare from the young M dwarf binary DG CVn - Fender, R.; Anderson, Gemma; Osten, R.; Staley, T.; Rumsey, C.; Grainge, K.; Saunders, R. (Wiley-Blackwell Publishing Ltd., 2014)
On 2014 April 23, the Swift satellite detected a gamma-ray superflare from the nearby star system DG CVn. This system comprises an M-dwarf binary with extreme properties: it is very young and at least one of the components is a very rapid rotator. The gamma-ray superflare is one of only a handful detected by Swift in a decade. As part of our AMI-LA Rapid Response Mode, ALARRM, we automatically slewed to this target, were taking data at 15 GHz within 6 min of the burst, and detected a bright (~100 mJy) radio flare. This is the earliest detection of bright, prompt, radio emission from a high-energy transient ever made with a radio telescope, and is possibly the most luminous incoherent radio flare ever observed from a red dwarf star. An additional bright radio flare, peaking at around 90 mJy, occurred around one day later, and there may have been further events between 0.1-1 d when we had no radio coverage. The source subsequently returned to a quiescent level of 2-3 mJy on a time-scale of about 4 d. Although radio emission is known to be associated with active stars, this is the first detection of large radio flares associated with a gamma-ray superflare, and demonstrates both feasibility and scientific importance of rapid response modes on radio telescopes. © 2014 The Authors.